The Effect of Arm Postures and Garment Style on Local Mobility and Thermal Insulation. Issue 1 (January 2022) - Zhang, Zhaohua; Ni, Jun; Zhou, Ying
Heat transfer in clothing can be influenced by posture change of the human body and garment pattern design. In this study, the volume of the air gaps and the contact area were investigated for different arm postures of a thermal manikin using a three-dimensional body scanner, and the effect of garment pattern design was analyzed. Furthermore, the local thermal insulation of different body parts of the thermal manikin was tested for six kinds of arm postures when the manikin was dressed in various experimental garments. Both arm postures and garment styles had a strong effect on the local air gap distributions. The air gap volume decreased, and the contact area increased with the growth of protraction angles of arms. The human tests also indicated that the range of arm motion was improved, and better flexibility was perceived compared with the original style. A significant positive correlation between thermal insulation and air gap volume ( r = 0.753, p < 0.001) was found.